2008
DOI: 10.1200/jco.2007.13.7349
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Palifermin and Concurrent Chemoradiation in Head and Neck Squamous Cell Carcinoma

Abstract: Ten once-weekly doses of palifermin at 60 microg/kg were well tolerated. Most patients completed treatment, but palifermin did not reduce the morbidity of concurrent chemotherapy and radiotherapy. Future studies should evaluate higher palifermin doses with longer and more standardized assessment of acute mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 29 publications
(8 reference statements)
0
48
0
Order By: Relevance
“…In addition to the results of the study by Brizel et al [42], in which post hoc analysis suggested that palifermin was marginally effective to reduce the duration of oral mucositis in hyperfractionated RT for H&N tumors, two publications of large multicenter, double-blind RCTs in patients treated with conventional 3D-chemoradiotherapy for H&N cancers became available after the cut-off date for the present update [92,93]. Henke et al [92] reported on patients that underwent postoperative CRT and received palifermin at doses of 120 μg/kg/week from 3 days before and continuing throughout the duration of treatment.…”
Section: Discussion and Late Breaking Reportsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to the results of the study by Brizel et al [42], in which post hoc analysis suggested that palifermin was marginally effective to reduce the duration of oral mucositis in hyperfractionated RT for H&N tumors, two publications of large multicenter, double-blind RCTs in patients treated with conventional 3D-chemoradiotherapy for H&N cancers became available after the cut-off date for the present update [92,93]. Henke et al [92] reported on patients that underwent postoperative CRT and received palifermin at doses of 120 μg/kg/week from 3 days before and continuing throughout the duration of treatment.…”
Section: Discussion and Late Breaking Reportsmentioning
confidence: 89%
“…No guideline could be provided for the use of palifermin in the setting of CT for solid and hematological tumors [38][39][40][41] due to insufficient evidence, although a single center RCT of 49 patients, using a single dose of palifermin (180 μg/kg) before each cycle of CT prevented mucositis in multicycle CT for sarcoma [41]. In addition, no guideline could be provided for the use of palifermin in H&N RT due to insufficient evidence [42].…”
Section: Resultsmentioning
confidence: 99%
“…Patients receiving hyperfractionated radiotherapy in a phase II study demonstrated a lower incidence of mucositis and shorter duration. 51 Another FGF family cytokine, basic FGF (bFGF) or FGF-2, is primarily found as a potent angiogenic growth factor because of its high capacity for inducing endothelial cell proliferation and migration as well as smooth cell proliferation, 52 and also accelerates second-degree burn wound healing and improves scar quality. 53 In burns, resurfacing with a dermal component is required, and bFGF stimulates wound healing and enhances human skin-derived mesenchymal stem cells under serum-free conditions in a dosedependent manner.…”
Section: Mitigators Of Radiationmentioning
confidence: 99%
“…However, a recent randomized phase 2 trial of weekly bolus i.v. palifermin in patients being treated with concurrent chemotherapy and radiation did not show evidence of mucosal protection, although studies at higher doses or higher frequency are ongoing (20).…”
mentioning
confidence: 99%